Heightening awareness for graduate students of the potential impacts of nanomaterials on human health and the environment using a theoretical-practical approach - De Melo, Nathalie F.S.; Fraceto, Leonardo F. [UNESP]; Grillo, Renato [UNESP] (American Chemical Society (ACS), 2017)
Rapid growth in nanoscience and nanotechnology in recent years has been accompanied by studies of the toxicity and potential impacts of nanomaterials on human health and the environment, but less has been done concerning education in this area. There is therefore a need for courses that address this theme at universities worldwide, in order to improve the training of students, stimulate research in this area, and make information available to the wider population. The present work proposes a model for a theoretical and practical course for graduate students, introducing basic concepts of nanotechnology, methods for the characterization of nanomaterials, environmental applications, and potential toxic effects of nanomaterials in the environment. The course includes five theoretical and practical topics: (i) nanomaterials characterization, (ii) practical approaches, (iii) environmental applications, (iv) nanomaterials toxicity, and (v) integrated studies. These are designed to provide the students with a clear understanding of nanoscience and nanotechnology, addressing the main aspects of toxicity of nanomaterials, their correlations with physicochemical properties, and potential solutions for environmental problems. The teaching model was delivered to Master's and Ph.D. students in a graduate program in Brazil, with highly satisfactory results.
Keywords: Environmental Chemistry; Graduate Education/Research; Hands-On Learning/Manipulatives; Interdisciplinary/Multidisciplinary; Laboratory Instruction; Nanotechnology